Factors Associated with Work Fatigue among Public Gas Station Operators in Kupang, East Nusa Tenggara - Maria Sahra Keron; Serlie K. A. Littik; Tadeus A. L. Regaletha (Journal of Health Promotion and Behavior, 2023)
Background: Public Gas Station (SPBU) is a public infrastructure to provide the fuel needs of the wider community. The high demand for fuel in Indonesia leads to demanding activities and potentially causes work fatigue to the workforce, especially operators. The study aims to analyze the correlation between working period, noise, workload, and work fatigue among the operators of the Public Gas Station in Kupang, East Nusa Tenggara. Subjects and Method: A cross-sectional study was conducted in Kupang, East Nusa Tenggara from October- November 2022. A total of 68 subjects consisted of 30 operators of 16 hours Public Gas Station; 38 operators of 24 hours Public Gas Station. The dependent variable was work fatigue. The independent variables were working period, noise, and workload. The data were collected using a questionnaire and analyzed using Spearman Correlation (rho). Results: Working period indicated a strong negative correlation with work fatigue, and was statistically significant (r= -0.74; p< 0.001). Noise revealed a weak negative correlation with work fatigue at gas station operators (r= -0.25; p= 0.837), while workloads showed a strong positive correlation with work fatigue at gas station operators, and the result was statistically significant (r= 0.850; p< 0.001). Conclusion: Working period, noise, and workload have a correlation with work fatigue among public gas station operators. Keywords: work fatigue, working period, noise, workload. Correspondence: Maria Sahra Keron. Public Health Study Program, Faculty of Public Health, Universitas Nusa Cendana, Kupang. Jl. Adi Sucipto Penfui, Penfui, Maulafa, 85001, Kupang, East Nusa Tenggara, Indonesia. Email: mariasahra08@gmail.com. Mobile: +6282145967956.